Role of Reference Group in Winning Banten Higher Education Service Market - Diqbal Satyanegara; Muhammad Johan Widikusyanto (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
The competitive conditions in the market of higher education services encourage every college in Banten to be able to retain students and acquire new students every year. The decision of the prospective student in determining the college of his choice is very important for the sustainability of every college in Banten. Understanding the factors that influence the prospective student's decision is expected to increase the competitive advantage of Banten college so as to win the target market. The purpose of this study is to test the model that explains the effect of education services and reference groups on the decision of prospective students in choosing a college. In addition, this study also aims to examine the role of mediation of reference groups that mediate the influence of educational services on the decision of prospective students in choosing a college. Survey research design is used to obtain data to be analyzed using SEM with the help of AMOS software. Questionnaires were distributed to 418 students from high school and vocational schools, both public and private in Banten. The SEM estimation results indicate that Service and Reference Group directly influence the decision of prospective students in choosing a college to continue their studies. In addition, the reference group proved to mediate the influence of the Services on the Decision of the Student Candidate. Thus, the reference group has an important role for the Education Services in determining the decision of the prospective student. Marketing communications should be directed in addition to the target market itself, but also to reference groups with positioning as distinct and superior educational services.